LOCAL GENIUS DALAM REVOLUSI MENTAL BANGSA PASCA REFORMASI - Samsudin Samsudin (Universitas Islam Negeri Fatmawati Sukarno, 2016)
The phenomenon of the nation caused mental shift multi-factor; globalization and modernization which led to social change, are already being felt since the post-reform government. To overcome this, the government announced a spectacular effort Mental Revolution. One possible solution is to create a revolutionary strategy (education) with the mental approach of local genius. Local genius was born as a product of noble culture and existence needs revitalization to rebuild the nation’s mental. This paper offers 9 (nine) revolutionary strategy (education) nation through the mental approach of local genius